A Rehabilitation Model Conducive to Postoperative Recovery of Endometrial Cancer Patients after Laparoscopy. (2nd September 2022) - Yang, Li; Han, Feng
Abstract : Although collaborative care is increasingly being implemented in the treatment of various diseases, there are currently no related studies on its effects in endometrial cancer patients after laparoscopic treatment. Thus, this study is aimed at investigating the significance of an integrated medical and nursing care model for women with gynecologic malignant tumors who underwent laparoscopic treatment. The patients were randomly divided into a medical-nursing integrated nursing group (study group) and a general nursing group (control group). Their serum carbohydrate antigen 19-9 (CA19-9), human epididymal protein 4 (HE4), CA15-3, and CA125 levels were measured at admission, 7 and 15 days after admission, and 30 days after discharge. Their first postoperative flatulence time, eating time, and hospitalization duration were recorded, and the self-rating anxiety scale (SAS) and self-rating depression scale (SDS) were used to evaluate the psychological state of the patients. A questionnaire survey was also used to evaluate their satisfaction with nursing. Adverse events within 2 years of follow-up were recorded. The results showed that the clinical performance of the study group was significantly better than that of the control group. Further, the study group demonstrated significantly lower serum tumor marker levels, SAS score, SDS score, and incidence of adverse events at 7 and 15 days after admission and 30 days after discharge and higher nursing satisfaction than the control group. Thus, the collaborative nursing mode might be more conducive to the recovery of women who have underwent laparoscopic treatment for gynecologic malignant tumors than normal routine nursing.